Satisfaction with life among adolescents from immigrant families in Portugal - Félix Neto (2001)
The aims of this study were to find out the degree of satisfaction with life among adolescents with immigrant background and the factors that map be related to the level of satisfaction with life among them. The study sample consisted of 313 Angolan, Cape Verdean, and Indian adolescents (mean age = 5.00 years; SD = 1.88), The mean duration of sojourn in Portugal for the sample was 8.2 years (SD = 4.8), They were asked to fill a questionnaire with several measures, including demographic information, satisfaction with life, identity, in-group and out-group social interaction, stressful experience acculturation, perceived discrimination, master?: self-esteem, and symptoms outcome. A control group involving 363 Portuguese youth were also included in the study. There were significant differences only between Portuguese and Angolan adolescents, in terms of level of life satisfaction, Portuguese adolescents were found to be more satisfied than Angolan adolescents from immigrant families. Whereas demographic factors accounted for just 6% of the variance explained demographic and psychosocial factors accounted for 31% of the variance explained. Mastery. was the most important factor related to life satisfaction. Gender, self-esteem, and living in an ethnically homogeneous neighborhood,were also found to be predictors of satisfaction with lift.